Re-visiting systematic observation: A pedagogical tool to support coach learning and development - Cope, Ed; Cushion, Christopher J.; Harvey, Stephen; Partington, Mark (Frontiers in Sports and Active Living, 2022)
Systematic observation has been one of the most employed data collection methods in sports coaching literature. Initial work, originally undertaken in the 1970’s, and gaining traction in the 80’s and 90’s looked to predominately offer descriptions of coaches’ behaviour. While this research continues to offer a significant contribution to the fields understanding of what coaches do during practice, systematic observation used only in this way has unfulfilled potential. The premise of this paper is to consider systematic observation as a coach development tool – a precedent which has been set in the literature. The arguments made are based on an alternative way of thinking about systematic observation, as a pedagogical tool supports coaches in better understanding themselves and their pedagogical practice. Principles of dialogic pedagogy are used as the basis of our argument whereby ‘researchers’ and ‘coaches’ work collaboratively to co-construct knowledge and support coach reflection, and ultimately develop coaches’ practice.